Вимірювання та аналіз метричних характеристик графів при використанні в інформаційних системах - Скульба, С. О. (ХНУРЕ, 2023)
The problem of using information technologies in the detection and analysis of requirements and preferences of users in social networks is being considered. Analysis has shown that approaches related to the calculation and analysis of metric characteristics of graphs can be used to solve this problem. Metric characteristics of graphs are quantitative indicators that allow measuring various aspects of graphs, such as size, connectivity, centrality, paths, distances, and others. Classification of metric characteristics based on their types (descriptive and quantitative characteristics) has been conducted.